2012
DOI: 10.1371/journal.pone.0035543
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Inhibitory Effect on the Biofilm Formation of Candida albicans by Liverwort Derived Riccardin D

Abstract: Riccardin D, a macrocyclic bisbibenzyl isolated from Chinese liverwort Dumortiera hirsute, has been proved to have inhibitory effect on biofilms formation of Candida albicans in in vitro study. Our present study aims to investigate the in vivo effect and mechanisms of riccardin D against C. albicans biofilms when used alone or in combination with clinical using antifungal agent fluconazole. XTT reduction assay revealed riccardin D had both prophylactic and therapeutic effect against C. albicans biofilms format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 39 publications
(42 reference statements)
0
15
0
Order By: Relevance
“…Moreover, C . albicans often adheres to form biofilms on many kinds of surfaces and interfaces (medical implants and catheters) [ 3 ]. Long filamentous structures called hyphae are the prominent feature of C .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, C . albicans often adheres to form biofilms on many kinds of surfaces and interfaces (medical implants and catheters) [ 3 ]. Long filamentous structures called hyphae are the prominent feature of C .…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 86 ] observed a total inhibition of the biofilm formation by using concentrations of 32 μ g/mL and 64 μ g/mL of pterostilbenes; at 16 μ g/mL, C. albicans biofilms were defective and only sparse cells were founded. In contrast, the same authors [ 87 ], evaluating the effect of riccardin D on anti- Candida biofilm formation, did not observe a complete growth inhibition by using a concentration of 64 μ g/mL.…”
Section: Clinical Importance Of In Vivo Studiesmentioning
confidence: 89%
“…Laser beams with 488-and 555-nm excitation wavelengths were used for FDA and PI imaging, respectively. FDA was hydrolyzed by viable cells, resulting in the accumulation of green fluorescence, whereas PI stained the dead cells (30).…”
Section: Methodsmentioning
confidence: 99%
“…A morphological study under a microscope showed radial colonies of untreated C. albicans cells with feathery edges on solid Spider medium (Fig. 7b), indicative of true hyphal growth (30,31). At the lowest concentration of 8 g/ml, EE blocked hyphal formation; however, pseudohyphae with constrictions at sites of septation were observed (5,9).…”
Section: Figmentioning
confidence: 99%